2016
DOI: 10.1159/000445241
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Genomic Research in Athletic Performance and Adaptation to Training

Abstract: Despite numerous attempts to discover genetic variants associated with elite athletic performance, an individual's trainability and injury predisposition, there has been limited progress to date. Past reliance on candidate gene studies focusing predominantly on genotyping a limited number of genetic variants in small, often heterogeneous cohorts has not generated results of practical significance. Hypothesis-free genome-wide approaches will in the future provide more comprehensive coverage and in-depth underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 21 publications
0
61
0
Order By: Relevance
“…However, we, and others, have reported large individual variability for the changes in BRMs and ucOC in response to similar exercise [9,6,7,10,8,11]. Indeed, some individuals are 'low-responders' (do not increase some aerobicrelated traits in response to exercise training), while others respond well or very well ('highresponders') to similar exercise, and this is, at least partly, likely due to genetic variability [12].…”
Section: Introductionmentioning
confidence: 65%
“…However, we, and others, have reported large individual variability for the changes in BRMs and ucOC in response to similar exercise [9,6,7,10,8,11]. Indeed, some individuals are 'low-responders' (do not increase some aerobicrelated traits in response to exercise training), while others respond well or very well ('highresponders') to similar exercise, and this is, at least partly, likely due to genetic variability [12].…”
Section: Introductionmentioning
confidence: 65%
“…According to recent literature data we can assume that rare and extreme phenotypes of elite athletes are based on rare functional changes or mutations that arise and are selected fairly recently in the course of human history, as these SNPs or mutations were detected only in some global regions. This concept is quite close to the idea used to detect hereditary diseases caused by mutations in single or multiple genes [47].…”
Section: Regional Aspects Of Sports Medicinementioning
confidence: 82%
“…However, in recent years, along with that began to appear some attempts to use analysis of genome-wide Association (GWAS) [15,33,47].…”
Section: Regional Aspects Of Sports Medicinementioning
confidence: 99%
“…Since endurance sports are characterized by increased cardiorespiratory capacity, genetic predisposition into elite endurance performance is also expected to be genetically influenced (21). However, genetic studies of elite athletic endurance showed inconsistent results (10,(21)(22)(23). The aims of this study were to carry out the largest GWAS study of elite European athletes to date using a unique SNP microarray that is enriched with genes involved in different metabolic pathways with direct influence on various physiological pathways characteristic of elite athletes.…”
Section: Discussionmentioning
confidence: 99%